Migrations and Spirituality in Europe: A Catholic Voice Inspired by the Thought of Pope Francis - Sawa, Przemysław (Ecumeny and law, 2021)
Europe has been experiencing crisis caused by migrations, especially from Africa and the Middle East. This is not only an economic problem, but a cultural, social, and religious issue as well. Therefore, a proper approach to migration cannot overlook the broadly understood religiousness and spirituality. Rooted in the Christian experience, Europe cannot ignore the significant message of the Word of God and the teaching of the Church on migration and its various dimensions. Thus, Catholics and other Christians are required to care for their own spirituality, create the culture of coming together that leads to peace, and stay open to ecumenical and interreligious dialogue which fosters exchange of spiritual gifts. Protection of family and support to integral development of human life are special areas where people can join forces and work together. This requires proper formation and being open to God’s help.